A radical awakening - Tsabary, Shefali, 1972- (Yellow Kite, 2021)
"Dr. Shefali Tsabary was 44 years old when she had an epiphany: the only person stopping her from harnessing her inner power was herself. Awoken to the patriarchal forces that shape female consciousness, Dr. Shefali dedicated her life to inspiring women to take back their power and liberate themselves mentally, spiritually, and emotionally. A Radical Awakening not only lays out a path to heal a woman's own wounds and those of women collectively, it prepares her to discover her own powers so that she may bring healing to others and the planet around her. Dr. Shefali Tsabary guides women through the process of uncovering the purpose that already exists within and harnessing the power of authenticity in every area of life. The result is an eloquent and inspiring, practical and accessible tool containing real-life examples and personal stories from Dr. Shefali's experience as a woman and clinical psychologist that show the extraordinary power of awakening your conscious self"--